Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan pada Perusahaan Sektor Energi yang Terdaftar di ISSI Tahun 2019-2022 - Cindy Permata Putri; Putri Syifa Amalia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of the fraud hexagon model, namely stimulus (pressure) proxied by financial stability, opportunity (opportunity) proxied by ineffective monitoring, rationalization (rationalization) proxied by change in auditor, capability (ability) proxied by change in director, ego ( arrogance) is proxied by the frequent number of CEO's picture, and collusion is proxied by state-owned enterprises in detecting potential fraud in financial statement. The sample of this study is energy sector companies listed on the Indonesian Sharia Stock Index (ISSI) in 2019-2022. This study uses secondary data, namely financial reports and annual reports. Based on the purposive sampling method, the number of companies sampled in this study was 27 companies out of a total of 34 companies registered and analyzed using multiple linear regression analysis using the SPSS 25 program. The results of this study found that the stimulus element proxied by financial stability had a significant effect on fraudulent  financial statements. Meanwhile, ineffective monitoring, change in auditor, change in director, frequent number of CEO's picture, and state-owned enterprises have no significant effect on fraudulent financial statement in energy sector companies registered with ISSI in 2019-2022.